Behind Quality Learning: The Strategic Role of Educator–Staff Synergy - Erni Suherni; Wahab (Universitas Nurul Jadid, 2025)
This study aims to analyze the quality of work interaction between educators and education staff and their contribution to improving the quality of learning at SD Negeri 10 Delta Pawan Ketapang. With a qualitative approach to field studies, data is collected through in-depth interviews, non-participatory observations, and documentation studies, then analyzed using thematic techniques. The results of the study show that open communication, participatory leadership of school principals, and a good understanding of each other's roles are the main factors in creating positive synergy. Education personnel not only carry out administrative functions, but also contribute directly to supporting the learning process technically and logistically. This synergy can be seen in various forms of work interaction, ranging from managing academic administration, scheduling lessons, to extracurricular activities, and handling emergencies. However, challenges such as miscommunication between units and differences in role perceptions are still obstacles that need to be managed systematically. This research suggests the need for regular cross-functional communication forums and collaborative training to strengthen synergistic roles in school governance. The practical and theoretical implications of this study confirm the importance of building mutually respectful and clarity-based working relationships to create a conducive school climate and sustainably improve the quality of learning.